Pengelolaan Situs Megalitik Tutari : Studi Pengembangan - Djami, Erlin Novita Idje (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2009)
Compared with other megalithic sites in Indonesia, Tutari site has its uniqueness in the drawings that can be found on rock’s hunks that widely cover the area, some arranged temugelang rocks, a pair of stones in a row, some carved stones and a group of menhirs that topped the hill. Archeological researches found that Tutari site was a center for religious activities of Tutari’s people. But the site was destroyed long ago due to the war brought by the Ebe tribe from Kwadeware (anchestors of Doyo’s people) that vanished the Tutari tribe. Since then, the site was abondoned until it was found and then confirmed as a protected cultural heritage. It is necessarily for the site to have a protective model to ensure its preservation. For the objective, the site needs to be divided into 3 group zones which are core, support and development zone. The division surely to be followed by continuum operation supported by structure and substructure to make the site can be fully developed to enrich our cultural landscape and to add substantial value to local tourism.